2004
DOI: 10.1111/j.1744-7348.2004.tb00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hot water drenches of Anthurium andraeanum plants against the burrowing nematode Radopholus similis and plant thermotolerance

Abstract: Hot-water drench treatments were evaluated for disinfesting roots of potted anthurium Anthurium andraeanum of the burrowing nematode Radopholus similis. A continuous drench of roots and media in pots with 50°C water for 5 to 20 min eliminated or reduced nematode populations to < 1 g -1 of dry root. A second hot water drench, 2 months after the first drenching, tended to increase the efficacy of the heat treatment. A few survivors persisted in the roots and/or stems of a few plants 2 to 4 months after heat trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Baermann funnels (Viglierchio and Schmitt 1983) were used to separate nematodes from the precipitation and microscope inspection was employed. If there were nematodes in roots, the roots were treated to remove nematodes (Tsang et al 2004). All noncontaminated seedlings were grown in sterilized soil medium for 15 days for later use.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Baermann funnels (Viglierchio and Schmitt 1983) were used to separate nematodes from the precipitation and microscope inspection was employed. If there were nematodes in roots, the roots were treated to remove nematodes (Tsang et al 2004). All noncontaminated seedlings were grown in sterilized soil medium for 15 days for later use.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Complete mortality of J2 of M. incognita was achieved at 44 and 45 o C when treated for one hour. Tsang et al (2003;2004) showed that hot water drenches disinfect roots and media of potted bamboo or palms by eliminating all the burrowing nematode, Radopholus similis. They found that a continuous hot water (50°C) drenching of either bare roots or media in pots for 15 min (bamboo palm) or 13 min (fishtail palms) successfully eliminated all burrowing nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Baermann funnels were used to separate the nematodes from the precipitate, and a microscopic inspection was performed [ 28 ]. If nematodes were present in the roots, the roots were soaked in hot water at 62°C to remove the nematodes [ 15 ]. All of the uncontaminated seedlings were grown in sterilized soil medium for 15 days for later use.…”
Section: Methodsmentioning
confidence: 99%